Amphiphilic hyaluronic acid derivative with the bioreducible bond: Synthesis and its implication for intracellular drug delivery - Shin, Jung Min; Hwang, Seung Rim; Heo, Roun; Saravanakumar, G.; Park, Jae Hyung (Polymer degradation and stability, 2014)
Since most of the anticancer drugs exert their action in the intracellular environment, it is imperative to deliver them selectively inside the cancer cells for effective therapy. In an attempt to develop the potential carrier for intracellular drug delivery, we prepared the amphiphilic hyaluronic acid conjugate (HA-SS-DDT) bearing the disulfide bond which could be selectively cleaved at the intracellular environment. Owing to its amphiphilicity, the HA-SS-DDT conjugate formed self-assembled nanoparticles in an aqueous condition. The nanoparticles were stable under the physiological condition (pH 7.4, 37 °C) for at least five days. Doxorubicin (DOX), chosen as the model anticancer drug, was effectively encapsulated into HA-SS-DDT nanoparticles with high efficiency (>70%) by the oil-in-water emulsion method. In the physiological solution (PBS, pH 7.4), DOX was released from HA-SS-DDT nanoparticles in a sustained manner. Interestingly, in the presence of 10 mM glutathione, a peptide abundant in the cytoplasm of the cancer cell, the release rate of DOX remarkably increased, which was due to disintegration of nanoparticles by the cleavage of the disulfide bond. DOX-loaded HA-SS-DDT (HA-SS-DDT-DOX) nanoparticles were efficiently taken up by squamous cell carcinoma (SCC7) cells via receptor-mediated endocytosis, followed by rapid release of DOX in the cytoplasm of the cells. Overall, these results indicate that HA-SS-DDT nanoparticles have promising potential as the carrier for intracellular DOX delivery.